A Completely Reimplemented MPI Bioinformatics Toolkit with a New HHpred Server at its Core. Issue 15 (20th July 2018) - Zimmermann, Lukas; Stephens, Andrew; Nam, Seung-Zin; Rau, David; Kübler, Jonas; Lozajic, Marko; Gabler, Felix; Söding, Johannes; Lupas, Andrei N.; Alva, Vikram
Abstract: The MPI Bioinformatics Toolkit (https://toolkit.tuebingen.mpg.de ) is a free, one-stop web service for protein bioinformatic analysis. It currently offers 34 interconnected external and in-house tools, whose functionality covers sequence similarity searching, alignment construction, detection of sequence features, structure prediction, and sequence classification. This breadth has made the Toolkit an important resource for experimental biology and for teaching bioinformatic inquiry. Recently, we replaced the first version of the Toolkit, which was released in 2005 and had served around 2.5 million queries, with an entirely new version, focusing on improved features for the comprehensive analysis of proteins, as well as on promoting teaching. For instance, our popular remote homology detection server, HHpred, now allows pairwise comparison of two sequences or alignments and offers additional profile HMMs for several model organisms and domain databases. Here, we introduce the new version of our Toolkit and its application to the analysis of proteins. Graphical Abstract: Highlights: The MPI Bioinformatics Toolkit offers a wide range of interconnected, state-of-the-art tools (e.g., HHpred, HHblits) for the advanced bioinformatic analysis of proteins. We have replaced the first version with an entirely new one that is faster and more sustainable. The new user interface is specifically designed to be intuitive to casual users. Our new HHpred server offers improved features and additional databases. To facilitate teaching, we now cache results of all submitted jobs and offer them for reuse.